Permata negara Tun Dr. Mahathir bin Mohamad [ - Azizul Rahim Saedin; Syed Othman Syed Ahmad (Produksi Filem Cipta, 2004)
Video CD.; DVD player compatible; however may not be compatible with all DVD players